Uso de terapias complementares no manejo de náuseas e vômitos induzidos por quimioterapia em mulheres com câncer de mama: uma revisão de escopo - Lima, Karen Rayara Bezerra (2024)
Breast cancer is considered a public health problem and, among all types of cancer, it is the one that most affects women around the world. Chemotherapy treatment for breast cancer has consequences marked mainly by hematological and gastrointestinal toxicities, which lead to chemotherapy-induced nausea and vomiting (CINV). Despite the use of antiemetic drugs considered effective in the prevention and treatment of CINV, inadequate control of these symptoms is still observed. In view of this, the search for holistic approaches to managing these symptoms has led to the use of complementary and alternative therapies alongside conventional therapies. From this perspective, this study aimed to map to the use of Alternative and Complementary Medicine (CAM) in the management of CINV in women with breast cancer. A scoping review study was used based on the methodological recommendations proposed by the JBI and the PRISMA-ScR guideline for scoping reviews. The inclusion and exclusion criteria for studies were established according to the acronym PCC and the search was carried out in 7 databases and 1 electronic repository. The selection was carried out by two independent reviewers with the help of Rayyan software. The main results were extracted and analyzed using the deductive qualitative content analysis technique. 39 studies were included, most of which were published in Iran, 15.38% published in 2015 and 79.49% randomized clinical trials. Based on the thematic analysis, the complementary therapies studied were organized into: manipulative and body practices; mind-body practices; biological practices and energetic practices. There is a high prevalence of nausea and vomiting after chemotherapy such symptoms are related to high doses of emetogenic antineoplastic agents. Studies show that the use of complementary and alternative therapies, whether manipulative and body practices, mind and body practices, biological practices, or energetics, are useful in reducing nausea and emesis, alone or in combination with antiemetic medications.